(untitled) (AYUSHDHARA, 2024)
Traditional medicinal system of India consist variety of natural herbs which are playing significant role in human health. Among them Enicostemma littorale Blume is one the herbaceous plant of the Gentianaceae family. The biter nature plant help in curing fever, act as a laxative, useful in skin disorders, rheumatism, snake bite, abdominal disorders, diabetes, obesity and in many more diseases. The plant used in folklore since long time in many diseases. The plant constituents having antimicrobial, antioxidant, antiulcer, anti-inflammatory, hypolipidemic, hypoglycaemic, hepatoprotective and antitumor activity. This review consists of detail description along with its literature review, ethnobotanical uses, phytochemical, pharmacological properties, and toxicological study of Enicostemma littorale Blume. The methodology adopted in this review is using Ayurvedic literature and modern scientific research-based publications including journal and periodicals. This review provide base for future research work in different aspect in the field of drug research.